Regional anesthesia as a safe option in patient with limb girdle muscular dystrophy undergoing total abdominal hysterectomy: A case report and case review. Issue 11 (6th November 2022) - Devkota, Sagar; Shrestha, Sangeeta; Gurung, Tara; Shrestha, Saurav
Abstract: Regional anesthesia can be a very safe option in patients with limb girdle muscular dystrophy undergoing lower abdominal surgeries as general anesthesia and volatile anesthetic agents are associated with increased risk of malignant hyperthermia and rhabdomyolysis.